Perencanaan Pembangunan Infrastruktur di Desa Sukatani Kabupaten Garut - Miman Nurdiaman; Ade Purnawan; Regina Fia Lestari Sudirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
The process of infrastructure development planning in Sukatani Village, Cisurupan Subdistrict, Garut Regency in 2019 is in accordance with applicable regulations, namely Minister of Domestic Affairs Regulation No. 114 of 2014 concerning Guidelines for Village Development, where planning is carried out starting from hamlet compound, village consultation and village development planning deliberations. The purpose of this study was to determine how the process of infrastructure development planning in Sukatani Village, Cisurupan District, Garut Regency and its inhibiting factors. Researchers used qualitative research methods. In the selection of informants purposively. The techniques used by researchers in data collection are interviews, observation and documentation with interactive analysis techniques. The results showed that in the village development planning stage the Sukatani village government focused on the construction of village roads and environmental roads as a means of public transportation, with consideration that these were in line with the priorities and needs of the Sukatani Village community. In the planning process found inhibiting factors, namely the absence of community self-help funds, lack of socialization of implementation and the village government did not involve the community in deciding the priority of infrastructure development needed by the community, causing a lack of participation in the implementation of infrastructure development. The advice that can be raised by Sukatani Village Government is to intensively socialize the Village Government Work Plan (RKP) and its financing budget through a website-based village information system, village information boards, and other media according to village conditions. Sukatani Village Government should involve the community in determining the priorities of infrastructure development so that the community knows clearly the reasons for determining the priorities for infrastructure development. Providing understanding to the community that the Village Fund is only an incentive or stimulus to increase community participation..